2011
DOI: 10.1186/1471-2431-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic ability of neutrophils and monocytes in neonates

Abstract: BackgroundInfections by a variety of pathogens are a significant cause of morbidity and mortality during perinatal period. The susceptibility of neonates to bacterial infections has been attributed to immaturity of innate immunity. It is considered that one of the impaired mechanisms is the phagocytic function of neutrophils and monocytes. The purpose of the present study was to investigate the phagocytic ability of neonates at birth.MethodsThe phagocytic ability of neutrophils and monocytes of 42 neonates was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 35 publications
5
62
0
1
Order By: Relevance
“…Adult monocytes can differentiate into macrophage and dendritic cells but they also scavenge toxins, produce cytokines, growth factors, reactive oxygen species, nitric oxide, prostaglandins, complement and proteolytic enzymes (see references (Auffray et al, 2009; Geissmann et al, 2008) for recent reviews) and can function as antigen presenting cells (Van Voorhis et al, 1983). In many respects, monocytes within HUCB are indistinguishable from adult monocytes (Filias et al, 2011; Gille et al, 2009), but they are not stimulated by hepatocyte growth factor (Jiang et al, 2001), produce fewer dendritic cells compared to adult monocytes (Liu et al, 2001) and also produce lower concentrations of pro- and anti-inflammatory cytokines (Brichard et al, 2001; Jiang et al, 2001; Le et al, 1997). A recent report in a model of diabetic retinopathy demonstrated that CD14+ HUCB cells became alternatively activated M2 macrophage that stimulated the resident myeloid cells to also become alternatively activated (Marchetti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Adult monocytes can differentiate into macrophage and dendritic cells but they also scavenge toxins, produce cytokines, growth factors, reactive oxygen species, nitric oxide, prostaglandins, complement and proteolytic enzymes (see references (Auffray et al, 2009; Geissmann et al, 2008) for recent reviews) and can function as antigen presenting cells (Van Voorhis et al, 1983). In many respects, monocytes within HUCB are indistinguishable from adult monocytes (Filias et al, 2011; Gille et al, 2009), but they are not stimulated by hepatocyte growth factor (Jiang et al, 2001), produce fewer dendritic cells compared to adult monocytes (Liu et al, 2001) and also produce lower concentrations of pro- and anti-inflammatory cytokines (Brichard et al, 2001; Jiang et al, 2001; Le et al, 1997). A recent report in a model of diabetic retinopathy demonstrated that CD14+ HUCB cells became alternatively activated M2 macrophage that stimulated the resident myeloid cells to also become alternatively activated (Marchetti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic substrate in PMR is synovitis characterized by vascular proliferation and infiltration of macrophages and lymphocytes [8]. However, the function of these infiltrating phagocytes remains 1 unclear. There is only one study in which neutrophil chemotaxis has been studied, in 8 patients with active PMR, and it was found to be normal [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors contribute to the efficient function of the phagocytic system. These factors include the presence of an adequate number of monocytes and neutrophils in the peripheral blood, the ability to respond to signals from sites of inflammation, induction of migration to these sites, and the capacity to ingest and kill the invader microorganisms [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that sapphire puppies are characterized by increased embryonal and early postnatal mortality as well as low weight at birth (2). In this connection it is important that the phagocytic ability of leukocytes in neonatal animals correlates with birth weight (19). Sapphire puppies in the first 10 days of life demonstrated retarded growth.…”
Section: Discussionmentioning
confidence: 99%